Discovery of the spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Laos, with the description of three new species - Loktionov, Valery M. (Zootaxa, 2021)
The genus Telostholus Haupt, 1929 is newly reported from Laos, with three species which are newly described and illustrated: T. kubani Loktionov, sp. nov., T. lao Loktionov, sp. nov., and T. leleji Loktionov, sp. nov. A key to the males is given.